Simple Multi-Attribute Rating Technique (Smart) Decision Making for Technology Selection of Real-Time Well Monitoring Project - Deni Eka Prasetya (Journal of International Conference Proceedings (JICP), 2019)
The real-time data availability is very important for analysis and decision-making process in oil and gas industry. This research objectives are to identify the major root cause of oil production loss and selecting the best alternative of Supervisory Control and Data Acquisition (SCADA) technology for real-time oil wells monitoring project. The manual wells monitoring is one of major contributor for oil production loss causes. The licensed frequency radio modem is selected SCADA technology based on Simple Multi-Attribute Rating Technique (SMART) process combined with the cost and benefit analysis. The implementation plan will be focus on project integration management with risk assessment recommendations.